THE DYNAMIC INTERPLAY OF LINGUISTIC DIVERSITY AND INFLUENCE ON THE SPEAKING SKILLS OF ESL LEARNERS IN THE CLASSROOM - Ishfaque Ali Kalhoro; Zaheer Ahmed Bango; Sonal Khan Maitlo; Abdul Rasheed Soomro (International Journal of Contemporary Issues in Social Sciences, 2024)
The objective of this study was to explore the dynamic interplay of linguistic diversity and influence on the speaking skills of ESL learners in the classroom in district Khairpur Mir’s Sindh, Pakistan. Employing a qualitative research method, the investigation focused on ESL learners from two secondary and higher secondary schools. Employing a survey approach, the researcher disseminated face to face questionnaire containing seven closed-ended questions to 80 participants of both sections to male students for data collection. The collected data underwent analysis in excel using tables. The outcomes reveal that speaking skills are being affected due to first language use; class environment, cultural influences, first language instructions and cognitive processing are substantial determinants affecting the speaking skills of ESL learners. Furthermore, the research puts forth practical and dynamic recommendations to address the language diversity hurdles impacting the speaking proficiency of second language learners, offering valuable insights for decision-makers in academia, individuals, teachers, and other stakeholders.